The Ins and Outs of Alpha-mangostin’s Potential as an Antimalarial - Tjahjani, Susy; Hermanto, Faizal; Muchtaridi, Muchtaridi; Aulifa, Diah Lia; Ahsanul Haq, Fahmi (Jurnal Kesehatan Masyarakat, 2025)
Malaria drug resistance, including to development of resistance against artemisinin based treatments, poses a major challenge to elimination efforts. Alpha-mangostin, an antioxidant with in vitro antimalarial activity, is hindered by its poor solubility. This study explores the antimalarial effects of water-soluble alpha-mangostin chitosan-alginate nanoparticles (ACAN) in mice with berghei malaria. Mice were treated with various doses of ACAN, compared to alpha-mangostin in polyethylene glycol (PEG), as well as in corn oil (ACO) and chloroquine as a standard. Growth inhibition rates were assessed, revealing no inhibition in the PEG and normal control (NC) groups, while ACO was less active. The effective dose 50 (ED50) of ACAN was 264.5 mg/kg BW, containing only 15.87 mg of alpha-mangostin, suggesting that alpha-mangostin in ACAN may offer promising in vivo antimalarial activity. Further investigation is needed.